Analysis of relationships between perimenopausal symptoms and professional functioning and life satisfaction - Subjective perception of the dependence in women aged 40+ - Iwona Nowakowska; Renata Rasińska; Maria Danuta Głowacka (Nofer Institute of Occupational Medicine, 2015)
Background: The aim of the study was to analyse and present the opinions of women in perimenopause on subjectively perceived symptoms characteristic of the climacteric period, and connected with their professional functioning, as well as to evaluate the effects of selected variables on the incidence and severity of these symptoms and the women's life satisfaction. Material and Methods: The study included 250 professionally active women in perimenopausal age (40-57 years). The study used the Satisfaction with Life Scale (SWLS) to evaluate life satisfaction of women and the Kupperman Index (KI) as quantitative and qualitative self-assessment of climacteric symptoms. The authors also used a questionnaire of their own design that contains an index of defined symptoms of perimenopause, which warrants the use of Pareto-Lorenz analysis. Results: The obtained results prove the presence of statistically significant correlations between the occurrence and severity of menopausal symptoms and the place of enployment (p = 0.04912), gynecological care (p = 0.00325), hormone replacement therapy (HRT) (p = 0.01523) and assessment of life satisfaction (p = 0.0325). Among the symptoms particularly influencing effective professional functioning, women pointed out hot flashes, irritability, reduced concentration and coordination, sleep disturbances, and increased sweating. Conclusions: There is a statistically significant correlation between the woman's place of employment, gynecological care, HRT, the evaluation of life satisfaction and the severity of perimenopausal symptoms. A set of symptoms whose presence and severity influence the sense of life satisfaction and evaluation of professional functioning was observed. Among the most frequently reported symptoms that exert an adverse effect on professional functioning of women are: hot flushes, irritability, reduced concentration and coordination, sleep disturbances, and increased sweating. Med Pr 2015;66(3):351-358